(untitled) (Medical Forum Monthly, 2022)
Objective: The study was conducted to assess the ureteric stone complications (urinary tract infection & preterm delivery) particularly during the last trimester of pregnancy. Study Design: A retrospective cohort study Place and Duration of Study: This study was conducted at the Urology & Gynecology & Obstetrics Department of Mukhtar A Sheikh Hospital Multan from March 2020 to March 2021 for a period of one year. Materials and Methods: Total 400 pregnant women with no ureteric stones and 35 pregnant women with ureteric stones were included in the study. The inclusion criteria were the women who delivered a live and singleton infant and were presented with ureteric stones in the last trimester. The exclusion criteria were to exclude the women whose time of discharge at birth and gestational age at delivery were found to be inconsistent. Written permission to conduct the study was obtained from the Institutional Review Board and Ethical Committee. The data retrieved included the demographic variables, history of the patient, gestational age, outcomes, and all the associated risks of ureteric stone on preterm delivery. Besides this, the percentage analysis of the frequency of urinary tract infection (UTI) before delivery was also calculated in both groups. Results: The mean ages of the pregnant women presented with and without ureteric stones were 25 and 27 years respectively with a standard deviation of ±4.3 & ±5.2. It was observed that 12% (4) of the pregnant women with ureteric stone delivered preterm infants while only 5% (20) of the pregnant women without ureteric stone delivered preterm infants (p<0.001). Preterm PROM occurred in 3.4% (14) and 10% (3) of pregnant women that presented without ureteric stones & with ureteric stones respectively. A statistically significant difference was seen in the frequency of UTI in both groups with 5% (20) and 25% (9) pregnant women presenting with UTI among the ones with no ureteric stones and with ureteric stones respectively. Conclusion: The study concluded that there is a comparatively high risk of preterm delivery and urinary tract infection in women who present with complain of ureteric stone in the last trimester of their pregnancy.